PERSEPSI MAHASISWA TETANG ISLAMIC ENTREPRENEURSHIP - Abdullah Mujaddid (Universitas Muhammadiyah Gresik, 2020)
This research was conducted to find out how students 'perceptions about Islamic Entrepreneurship and whether the students' perceptions were in accordance with the college education they had received so far. This research uses a qualitative method with a descriptive analytic study approach, while the technique of collecting data through observation, interviews and documentation, while the technique of determining the researcher's informant uses a purposive sampling technique that is the sample is chosen based on the researchers' assessment that he is the right party to be the sample of his research. Determination of the informants chosen by the researchers themselves and the informant is considered to have known about the problem under study. As for the target selection of informants are Islamic Lecturers and Muhammadiyahan lecturers who are influential lecturers of entrepreneurship courses, as well as students of the 6th semester entrepreneurship study program at Muhammadiyah University Gresik. The results showed that the students of entrepreneurship at Muhammadiyah University Gresik generally understood the concept of Entrepreneurship and lack of understanding of the concept of Islam and its implementation in the concept of entrepreneurship and lack understanding of the concept of Islamic Entrepreneurship, because there is no Islamic Entrepreneurship model that is used as a reference in the learning system